Analysis of Teacher Assistants in Preventing Verbal Bullying in Elementary School Students - Santi, Wahyu Nur Santi; Sukma, Hanum Hanifa (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2024)
Language is a way for people to communicate between speakers and interlocutors; with language, people can understand what they are talking about. This study aims to describe the forms of verbal bullying behavior of students of SD Muhammadiyah Bausasran Yogyakarta and describe teacher assistance in preventing verbal bullying of students of SD Muhammadiyah Bausasran Yogyakarta. This research uses descriptive research with a qualitative approach. The data collection techniques used were observation, interviews, and documentation. This research uses source triangulation and technique triangulation to re-examine the data that has been researched. The results of this study are that Muhammadiyah Bausasran Yogyakarta Elementary School teachers have implemented teacher assistance by using good language politeness to prevent verbal bullying of class IV students. The forms of verbal bullying that occur at SD Muhammadiyah Bausasran Yogyakarta are mocking, making fun of, cheering, humiliating, and giving nicknames. Factors that influence verbal bullying are individual factors, family factors, peer factors, school factors, and mass media factors. The way teachers overcome verbal bullying that occurs in class IV of SD Muhammadiyah Bausasran Yogyakarta is by providing assistance to participants by using good language politeness.